The role of public policies to enhance innovation in low-tech small firms - Bonotto Barboz, Ricardo Augusto; Fonseca, Sergio Azevedo [UNESP]; Freitas Ramalheiro, Geralda Cristina de (Elsevier B.V., 2017)
The need for organizations to innovate has always been a major factor for business competitiveness. From the beginning of the 2000's this need has turned even more important, especially with the advent and widespread of innovations, intensifying competition and shortening the life cycle of products. It is perceived, however, that companies operating in more traditional sectors of the economy have higher barriers to innovative procedures, barriers increased and enhanced when it comes to the universe of micro and small enterprises (MSEs). These difficulties, by itself, support the need for policies and public interventions in order to minimize the barriers. In this context, this paper addresses a research which studied two innovation supporting programs in Brazil: the business incubation, with particular focus in the Business Incubator of the city of Araraquara; and the Brazilian Service for Technical Answers (SBRT) in this particular case represented by one of his agents, the Integrated Service of Technical Answers (SIRT) of the Universidade Estadual Paulista (UNESP/Araraquara). This study reports the virtues, the limitations and difficulties of these two instruments of public policy as potential or actual inducers to innovations in non-technological micro and small enterprises (MSEs). The research analyzed the types, sources and mechanisms used to promote innovations in the MSEs. The methodology comprised a qualitative research, exploratory, designed as a simple case study, with data collected through interviews and participant observation. It was found that the MSEs, even those who participate in public programs and policies, have many difficulties to operationalize innovation. It was noted also that the joining of the two instruments leveraged innovative activities. (C) 2016 Departamento de Administracao, Faculdade de Economia, Administracao e Contabilidade da Universidade de Sao Paulo - FEA/USP. Published by Elsevier Editora Ltda. This is an open access article under the CC BY-NC-ND license
Keywords: Public policies; Business incubators; Technical notes; Innovation networks; Low-tech small firms